2022
DOI: 10.1136/bmjgh-2021-008138
|View full text |Cite
|
Sign up to set email alerts
|

Use of traditional medicine and control of hypertension in 12 African countries

Abstract: BackgroundUse of traditional medicine (TM) is widespread in sub-Saharan Africa as a treatment option for a wide range of disease. We aimed to describe main characteristics of TM users and estimate the association of TM use with control of hypertension.MethodsWe used data on 2128 hypertensive patients of a cross-sectional study (convenience sampling), who attended cardiology departments of 12 sub-Saharan African countries (Benin, Cameroon, Congo, Democratic Republic of the Congo, Gabon, Guinea, Côte d’Ivoire, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…23 In Peru however, those unaware of their hypertension had the highest mean BP, followed by the treated, then those aware but not receiving treatment. 24 Treatment failure in our study could be explained by several patient-related factors including poor adherence which might be related to side effects and local beliefs or misconceptions around hypertension, [25][26][27] or a lack of awareness of the serious risks to their future health. Medication adherence is a vital component to treatment success which has been previously evaluated in The Gambia and found to be sub-optimal.…”
Section: Discussionmentioning
confidence: 84%
“…23 In Peru however, those unaware of their hypertension had the highest mean BP, followed by the treated, then those aware but not receiving treatment. 24 Treatment failure in our study could be explained by several patient-related factors including poor adherence which might be related to side effects and local beliefs or misconceptions around hypertension, [25][26][27] or a lack of awareness of the serious risks to their future health. Medication adherence is a vital component to treatment success which has been previously evaluated in The Gambia and found to be sub-optimal.…”
Section: Discussionmentioning
confidence: 84%
“…A lot of patients fear initiating antihypertensive treatment and commonly resort to traditional practices even after being initiated on treatment, as has been reported in a study in 12 African countries. 45 The limited understanding and the asymptomatic nature of the condition also has a big impact on medication adherence. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the prevalence of regular exercise among patients with HTN 11–13 ; however, these studies had small sample sizes and were limited to patients in low‐ and middle‐income countries, including Ethiopia, Iran, and China 11–13 . Moreover, medical resources, healthcare systems, and treatment strategies available in low‐ and middle‐income countries differ from those in high‐income countries 5,9,14–16 . Therefore, exercise habits in patients with HTN may differ among low‐, middle‐, and high‐income countries.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 , 13 Moreover, medical resources, healthcare systems, and treatment strategies available in low‐ and middle‐income countries differ from those in high‐income countries. 5 , 9 , 14 , 15 , 16 Therefore, exercise habits in patients with HTN may differ among low‐, middle‐, and high‐income countries. Hence, it is crucial to assess the proportion of patients engaging in exercise in each country in order to enhance the approach to exercise therapy in the healthcare system.…”
Section: Introductionmentioning
confidence: 99%